Mobile-permeable zones in the foundation of the north-eastern part of the Baltic Shield and the conditions for their localization - V. T. Filatova (Геофизический журнал, 2012)
On the example of the Kola region tectonophysical simulation has been performed, which provided discrimination of the structures draining the uplift of mantle basic-ultrabasic magmas. The research has been carried out on the basis of numerical simulation to reconstruct the zones of high permeability of the basement, which were formed in the Late Archean and predetermined the localization of tectonic magmatic processes in the region. For this purpose, quantitative models have been plotted of the strained-deformed state of the Earth's crust of the region taking into consideration its evolutionary development. The northeastern part of the Baltic Shield is treated as a non-uniform elastic body affected by volume forces and stresses specified at the boundary. The boundary value problem has been solved in terms of stresses. For the first time it is proposed to apply calculations of gradient stress fields to identify weakened zones in the basement. Two stages of the Archean period in the Kola region have been considered. Analysis of the results of numerical experiment conducted shows that the inception of the weakened zones in the Kola megablock basement, which predetermined location of the Kolmozero-Voronja and Tersky- Allarechka greenstone belts, occurred earlier than in the northern part of the Belomorian megablock involving the area of the Yona greenstone belt distribution. The methods elaborated can be applied as the ones of a rapid diagnosis to allocate the weakened zones in the basement and evaluate their permeability degree with the minimum time and resources required.